Child Care Availability, Quality and Affordability: Are Local Problems Related to Maternal Labour Supply - Gong, X; Weiss, A; Yamauchi, C; Breunig, R (My University, 2009)
We examine whether responses to survey questions about child care availability, quality, and cost, aggregated at the local geographical level, have any explanatory power in models of maternal labour supply. We find that married women who live in areas with more reports of lack of availability, low quality, or costly child care work less than women in areas with fewer reported difficulties with child care. We find this effect on both the hours of labour supplied and on the part-time/full-time choice. We find few effects for lone parents.
Economics Program, Research School of Social Sciences Working Paper
Keywords: Child Care -- Cost/affordability; Child Care -- Access/Availability; Child Care; Employment; Gender -- Female; Gender; Gender; Labour market; Employment; Child Care; Gender; Access/Availability; Female; Cost/affordability; Employment and unemployment; Gender